High-Risk Pregnancy: Associated Factors, Impacts, and the Importance of Prenatal Care - Felipe Mesquita Andrade, Alex; Dalla Bernardina Casotte , Marina; Xavier Valenzuela, Laura; de Aquino Maciel, Bianca; Rodrigues Ribeiro, Rhannielly; Khouri Fernandes, Rafaella; de Araújo Pereira, Luccas; Ribeiro, Juliana; Rodrigues de Mello, Elizangela; Soares Borges, Julia; Virginia Borges Souza de Aquino Coelho, Dioelen (Brazilian Journal of Implantology and Health Sciences, 2024)
This article addresses the theme of high-risk pregnancy, discussing its definition and the many factors that can lead a pregnancy to be considered risky. Based on the analysis of the data obtained through studies published in medical sites and journals, it was possible to correlate some factors, such as pre-existing conditions or those acquired during the pregnancy, to a greater risk during the course of the gestational period. The studies also show the possible ways to approach such factors when discovered, avoiding aggravations. Thus, the importance of thorough prenatal care becomes clear, in such a way as to allow the early discovery of any abnormalities, enhancing the chances for an efficient treatment that maintains the safety of the gestation.